Studies on the Biochemistry of Urokinase - Ong, Eng Bee; Soberano, Mercedes E.; Johnson, Alan J.; Schoellmann, Guenther (Thrombosis and Haemostasis, 1977)
Direct evidence for an active center histidine residue in urokinase (UK) was obtained with use of newly synthesized peptide chloroketones Ac-Gly-Lys-CH2C1 and Nle-Gly-Lys-CH2C1. Stoichiometric inactivation by DFP provided further evidence that UK is a serine protease. Essential histidine and serine residues were both located in the heavy chain of the 47,0 M. W.UK. The high M.W. form can be converted (catalytically) to the low M. W. form.9 partially purified human urinary UK preparations (5 with predominantly high M. W. UK), varying in purity and proportion of high and low M. W. forms, were found to be heterogeneous by a number of acrylamide electrophoretic procedures. 7 preparations had strikingly similar molar activities at excess substrate, except for the lower values found in 2 predominantly high M. W. UK preparations from the same supplier. 2 high M. W. UK preparations from another supplier showed a definite increase in activity when assayed at low plasminogen concentration, but this effect was abolished after gel filtration (Sephadex G-25), by further purification with affinity chromatography, or when assayed with excess plasminogen.The high and low M. W. forms of UK (47,000 and 33,400 M. W.), isolated and purified by Sepharose-EACA-agmatine affinity chromatography were shown to be homogeneous by Coomassie Blue staining after SDS-polyacrylamide gel electrophoresis (PAGE) and by 14C-DFP and 14C-NPGB incorporation before SDS-PAGE. Comparative properties of the high M. W. vs low M. W. forms were as follows: specific activity (104,000 IU/mg vs 226,000) ; 2 chains (33,100 and 18,600 M.W.) linked by disulfide(s) vs a single chain; pi 8.60 (major subform) and pi 8.90 (minor subform) vs pi 8.35, 8.60, 8.70 (major subform) and pi 8.05 (minor subform); and second order kinetics for DFP inactivation (400 vs 770 M−1 min−1). The molar activities were similar (9.6 × 109 and 10.2 × 109IUm/mole) for each form.